Fish Slicer - Jumain, Muhammad Nur Adib; Sanif, Muhammad Aizat Hanif; Lim, Davson Howel; Hassim, Hairul Mubarak (Multidisciplinary Applied Research and Innovation, 2022)
Fish cutting machine is used to slice fish into smaller pieces, and the machine vary from single blade machine and multiple blades machine. The fish slicing machine that is available in the market is heavy and has low level of portability, thus it only be used in a big fish supply industry. The Fish Slicer is designed with a light weight and small portable body frame compared to other machines available in the market. The machine is built-in with a single motor that runs the fish slot that holds the fish before entering the multiple cutting blades that slice fishes in to similar size. A test is performed, with average rotations per minute for fish cutter and fish slots are 3168 and 154 respectively. As a result, Fish Slicer fish slicing productivity is greater than traditional cutting methods. In short, the Fish Slicer is a portable machine and time saving that benefit fish market retailer and seafood restaurants by increasing fish slicing productivity.